PERILAKU KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN PARTISIPASI KERJA GURU DI SDN WATUKARUNG PRINGKUKU PACITAN - Teguh Teguh (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
Teachers who can help the leadership task optimally, it needs a leader who is able to direct and adjust the behavior of subordinates to achieve organizational goals to the fullest. This is a qualitative research, and an ethnographic design. Object of research are teachers of Watukarung elementary school. Interviewees in this study include the principal and teachers of Watukarung elementary school. Data collection are observations, interviews, and documentations. Validity data tested by triangulation. Site analysis Data. The results showed that: (1) the principal Watukarung elementary school in an effort to increase labor participation of teachers use a variety of styles in his leadership; (2) the principal Watukarung elementary school in an effort to increase labor force participation by using a democratic leadership style, discretionary, charismatic, participative and sometimes militaristic, it can be determined strategies undertaken; and (3) the principal of Watukarung elementary school in an effort increase in labor participation received very good response from teachers, school employees and even all citizens, it is because the principal made in accordance with desired by subordinates.